131k views
1 vote
By using the Chain Rule, differentiate with respect to x:

By using the Chain Rule, differentiate with respect to x:-example-1

1 Answer

1 vote

Answer:

y'=9x^2 *
√(2x^3 + 1)

Explanation:

y=(4x^3 - 2x^3 + 1)^3/2 ==>
√(?)=?^1/2

y'=3/2(4x^3 - 2x^3 + 1)^1/2 * (4x^3 - 2x^3 + 1)'

y'=3/2(2x^3 + 1)^1/2 * (12x^2 - 6x^2 + 0)

y'=3/2(2x^3 + 1)^1/2 * (12x^2 - 6x^2 + 0)

y'=3/2(2x^3 + 1)^1/2 * 6x^2

y'=3/2 *
√(2x^3 + 1) * 6x^2

y'=3/2 * 6x^2 *
√(2x^3 + 1)

y'=3 * 6x^2/2 *
√(2x^3 + 1)

y'=3 * 3x^2 *
√(2x^3 + 1)

y'=9x^2 *
√(2x^3 + 1)

User Henry Aspden
by
4.4k points